Access to government procurement opportunities and women empowerment in Kenya: policy interventions to bridge information gaps - Kiraka, Ruth N., Otieno, Hellen N.; Kiraka, Ruth N. (Strathmore University, 2023)
Public Procurement constitutes a strategic element of any economy. The level of public expenditure, if adequately and strategically managed through a sound procurement process can produce greater economic and social outcomes and impact. The Kenya Government initiated Access to Public Procurement Opportunities (AGPO) programme to facilitate enterprises owned by women, youth and people with disabilities to participate in government procurement opportunities, to economically empower them. This Policy Brief highlights information gaps in the AGPO programme that have undermined its uptake. It presents key findings of a research project that focused on the effectiveness of the AGPO initiative in enhancing women’s participation in public procurement and promoting their economic empowerment2 conducted in 25 counties. A key finding of the research was that the AGPO programme does contribute to women’s empowerment. However, there are information gaps and/or misinformation, that prevent many women entrepreneurs from participating in the programme. The Policy Brief offers recommendations on how these gaps can be addressed.
Policy brief